Socioeconomic status and its limited influence on perceptions of heated tobacco products and cigarettes: no relation with physical health, but association with mental health benefits and lower sensitivity to peer pressure - Kozela, Magdalena; Sytnik-Czetwertyński, Janusz; Polak, Maciej; Gradowicz-Prajsnar, Barbara; Rogala, Maciej (Frontiers in Public Health, 2025)
IntroductionSocioeconomic status is related with individuals’ attitudes toward health behaviors and perceptions of risk. This study investigated the relationships between socioeconomic status and perceptions of the impact of heated tobacco products (HTPs) and cigarette smoking on the physical, mental, and social well-being of users.MethodsA cross-sectional study was conducted using a population-based random sample of 2,500 HTP users and former smokers over the age of 25. The computer-assisted web interview (CAWI) method was employed to gather data. Information on gender, age, education, place of residence, income, and detailed perceptions of the impact of HTPs use and cigarette smoking on physical, mental, and social well-being was collected. A socioeconomic status score was derived based on education and income data. Multivariable multinomial regression analysis was used to assess the impact of socioeconomic status on perceptions of HTPs use and cigarette smoking in relation to physical, mental, and social well-being, controlling for age, place of residence, and perceived health status. The reference category was middle socioeconomic status and the middle category of perceived impact.ResultsA total of 2,254 participants were included in the analysis. Socioeconomic status was not related with perceptions of the impact of HTPs use or cigarette smoking on physical well-being. Compared to those with middle socioeconomic status, individuals with low socioeconomic status were more likely to perceive a positive impact of HTPs use on mental well-being (OR = 1.71, 95% CI: 1.12–2.60). Women with low socioeconomic status showed a stronger perception of being unaffected by peer pressure, both against smoking cigarettes and using HTPs (OR = 1.69, 95% CI: 1.11–2.57; OR = 1.53, 95% CI: 1.10–2.12, respectively).ConclusionWhile socioeconomic status did not differentiate perceptions of the impact of HTPs use or smoking on physical health, more tailored public health strategies that consider socioeconomic factors may be needed when addressing mental health perceptions and the influence of peer pressure.